Suppression and Replacement Gene Therapy for Autosomal Dominant Disease in a Murine Model of Dominant Retinitis Pigmentosa - Millington-Ward, Sophia (Nature Publishing Group, 2011)
For dominantly inherited disorders development of gene therapies, targeting the primary genetic lesion has been impeded by mutational heterogeneity. An example is rhodopsin-linked autosomal dominant retinitis pigmentosa with over 150 mutations in the rhodopsin gene. Validation of a mutation-independent suppression and replacement gene therapy for this disorder has been undertaken. The therapy provides a means of correcting the genetic defect in a mutation-independent manner thereby circumventing the mutational diversity. Separate adeno-associated virus (AAV) vectors were used to deliver an RNA interference (RNAi)-based rhodopsin suppressor and a codon-modified rhodopsin replacement gene resistant to suppression due to nucleotide alterations at degenerate positions over the RNAi target site. Viruses were subretinally coinjected into P347S mice, a model of dominant rhodopsin-linked retinitis pigmentosa. Benefit in retinal function and structure detected by electroretinography (ERG) and histology, respectively, was observed for at least 5 months. Notably, the photoreceptor cell layer, absent in 5-month-old untreated retinas, contained 3–4 layers of nuclei, whereas photoreceptor ultrastructure, assessed by transmission electron microscopy (TEM) improved significantly. The study provides compelling evidence that codelivered suppression and replacement is beneficial, representing a significant step toward the clinic. Additionally, dual-vector delivery of combined therapeutics represents an exciting approach, which is potentially applicable to other inherited disorders.